Insurance: is it better together? - E. A. Rusetskaya; D. A. Zakharova; A. A. Krechetova; A. I. Shchetinskaya; Ya. D. Gundar; K. S. Frolov (Вестник Северо-Кавказского федерального университета)
Introduction. In order to minimize certain risks of consumer loans, credit institutions impute to the insurance obligation to credit-borrowers. The current tariff policy of commercial insurers is in constant dynamic development due to deterministic factors (record growth of mortgage loan issuance, unreasonably high amounts of insurance remuneration to intermediaries, changes in standards for insurance of credit risks, etc.), which steadily affects the amount of insurance premiums of loan borrowers. Why some organizational-legal forms of insurers have developed despite high tariffs, while others have not? Can mutual insurance societies (MIS) be a better alternative to commercial insurance?Goal. The study intends to identify the potential reasons for the relatively insignificant share of MIS in the insurance market and to assess the attractiveness of the latter in increasing the efficiency of the insurance mechanism in the system of ensuring the financial security of citizens and economic entities.Materials and methods. The research is based on the analysis of the insurance market, by interpreting publicly available Internet data, their synthesis, comparison, measurement, classification and modeling of trends. The data is taken from official domestic and foreign sources; their value is determined by the methods of induction, deduction, correlation and content analysis, mathematical and statistical analysis.Results and discussion. In the course of the research, the most obvious areas of disagreement between insurers and their clients have been outlined. The factors contributing to the pricing of services in the insurance market, the relatively low share of the represented MIS and their services have been analyzed, as well as possible prerequisites for the emergence of the trend of radical changes in the structure of the national market of insurance services have been considered.Conclusion. The conducted research allows us to conclude that with positive dynamics of insurance culture and tightening of state regulation in the insurance industry, mutual insurance societies will enjoy relative popularity, thus stimulating the insurance market to adapt to changes, being more oriented to the needs of the client.